Dynamics of five grade leishmania epidemic model using fractional operator with Mittag-Leffler kernel - Zarin, Rahat; Khan, Amir; İnç, Mustafa; Humphries, Usa Wannasingha; Karite, Touria (Pergamon-Elsevier Science Ltd, 2021)
In this article, the Anthroponotic Cutaneous Leishmania transmission is discussed. In addition, a mathematical model for the Anthroponotic Cutaneous Leishmania transmission is developed and its qualitative behavior is considered. The threshold number R-0 of the model is derived using the next generation method. Local stability at disease free and endemic equilibrium point is carried out. Finally, the sensitivity analysis of the threshold number with other parameters is also taken into account. Several graphs of important parameters are also discussed. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: Mittag-Leffler; Sensitivity analysis; Hyers-Ulam stability; Approximation